Data phase synchronizers of closed loop - Reis, António (2018)
This work studies the data phase synchronizers of closed loop or data phase lock loop (DPLL). This synchronizer have all its blocks inside of the loop, for this reason it is called closed loop. The synchronizer is a loop with a phase comparator and VCO (Voltage Controlled Oscillator), that synchronizes the output feedback with the main input data. We consider four data synchronizers namely the analog, the hybrid, the combinational and the sequential. The objective is to study the four synchronizers and to evaluate their output jitter UIRMS (Unit Interval Root MeanSquare) versus input SNR (Signal to Noise Ratio).